Implikasi Filsafat Identitas Terhadap Perbedaan Ideologi Peran Gender di Era Digital - Helyatul Aulia Arifin; Isnaini Maulidariyanti; Muhammad Nor Aqli; Muhammad Riduan; Muhammad Syahidan; Nurhidayati (PT. Sharia Journal and Education Center, 2024)
Identity philosophy offers a framework for understanding how individuals define themselves and their roles in society, including in the context of gender. In the digital era, gender identity has become increasingly complex, covering a broad spectrum that goes beyond traditional binary categories. The ideological differences regarding gender roles between traditional views that base gender on biology and progressive views that view gender as a social construction are increasingly prominent in the digital space. Digital technology not only accelerates dialogue and transformation of understanding about gender but also strengthens ideological polarization.